LECTURER’S PERSPECTIVES ON THE USE OF ARTIFICIAL INTELLIGENCE TOOLS IN STUDENTS’ WRITING - Tri Yuli Ardiyansah; Riska Widiyanita Batubara (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The increasing intensity of students' use of various artificial intelligence technology instruments in the preparation of scientific papers at the tertiary level is the background to this research activity. These operational issues have triggered deep ethical concerns regarding the degradation of originality, the risk of plagiarism, and the high level of mechanical dependence of students on automated text results. The main focus of this scientific study is to investigate the perspectives of English lecturers on the use of artificial intelligence instruments in student academic writing activities at the University of Muhammadiyah Gresik. The research steps were carried out systematically using an integrated mixed-methods design with a questionnaire survey scheme and semi-structured interviews with nineteen purposively selected lecturers. Primary field data collection was obtained through closed-ended questionnaires and interview transcripts, which were then analyzed using descriptive statistics and thematic analysis methods. Quantitative data empirically revealed a high level of functional literacy of lecturers, where 84.2 percent were familiar with the generative application ChatGPT and 78.9 percent understood its mechanisms, but only 42.1 percent felt confident in identifying machine-intervention text. The main conclusion confirms that educators view this technology as a proportional, adaptive instructional supplement, not a substitute for critical thinking. Campus management is recommended to draft a rigorous process-based assessment system and strengthen institutional code of ethics regulations to responsibly optimize student digital literacy. ABSTRAK Meningkatnya intensitas pemanfaatan berbagai instrumen teknologi kecerdasan buatan oleh kalangan mahasiswa dalam penyusunan karya ilmiah pada jenjang perguruan tinggi melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu timbulnya kekhawatiran etis yang mendalam mengenai degradasi orisinalitas, risiko plagiarisme, serta tingginya tingkat ketergantungan mekanis mahasiswa pada hasil teks otomatis. Fokus utama kajian ilmiah ini adalah menginvestigasi perspektif dosen bahasa Inggris terhadap penggunaan instrumen artificial intelligence dalam aktivitas academic writing mahasiswa di Universitas Muhammadiyah Gresik. Langkah-langkah penelitian dijalankan secara sistematis menggunakan desain mixed-methods terpadu berskema survei kuesioner dan wawancara semi-terstruktur kepada sembilan belas dosen yang dipilih secara purposive. Pengumpulan data primer lapangan diperoleh lewat kuesioner tertutup dan transkrip wawancara, yang selanjutnya dianalisis menggunakan deskriptif statistik serta metode analisis tematik. Data kuantitatif secara empiris menyingkap tingkat literasi fungsional dosen yang tinggi, di mana 84,2 persen akrab dengan aplikasi generatif ChatGPT dan 78,9 persen memahami mekanismenya, namun hanya 42,1 persen yang merasa percaya diri mampu mengidentifikasi teks intervensi mesin. Simpulan utama menegaskan bahwa para pendidik memandang teknologi ini secara proporsional sebagai mitra suplemen instruksional yang adaptif, bukan pengganti nalar kritis. Manajemen kampus direkomendasikan merancang draf sistem process-based assessment yang ketat serta memperkuat regulasi kode etik kebijakan institusional guna mengoptimalkan literasi digital mahasiswa secara bertanggung jawab.